2013
DOI: 10.1590/s1516-14392013005000190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt-water fog on fatigue crack nucleation of Al and Al-Li alloys

Abstract: Fatigue and corrosion-fatigue tests were performed to quantify the fatigue properties of AA2524-T3 and AA2198-T851 Al alloys. High cycle axial fatigue tests were carried out under air and salt-water fog conditions. In air, the specimens were fatigue tested at a frequency of 50 Hz, using specimens with and without preconditioning in a salt spray chamber, and for the corrosion fatigue condition, the tests took place at a frequency of 30 Hz in a salt-water fog condition. In all cases it was used a sinusoidal wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…These IMs usually cause localized corrosion such as pitting corrosion, due to the electrochemical potential difference between the IMs and the matrix. A detailed study of the IM compounds present in the AA2524-T3 alloy are in line with the previous work presented elsewhere 9,15,[18][19] .…”
Section: Results E Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These IMs usually cause localized corrosion such as pitting corrosion, due to the electrochemical potential difference between the IMs and the matrix. A detailed study of the IM compounds present in the AA2524-T3 alloy are in line with the previous work presented elsewhere 9,15,[18][19] .…”
Section: Results E Discussionsupporting
confidence: 81%
“…In order to improve the durability of the aircrafts, the aeronautical industry has been constantly working on development of new advantageous aluminium alloys 9 . The AA2524-T3 (Solution Heat Treated and Cold Worked) alloy produced by ALCOA may be used as fuselage skin material and represents a potential replacement for the AA2024 alloy, widely used by the aircraft industry 9 . Recent publications showed that the fatigue behaviour of AA2524-T3 aluminium alloy is dependent on experimental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The 7081-T73511 aluminium alloy have already been studied by the present authors, namely in what concerns their global and localised corrosion processes and fatigue life (air, pre-corroded and salt-water fog conditions). As is already known, particles containing Fe and Cu elements are cathodic with respect to the matrix, promoting dissolution of the aluminium matrix [4,5]. Due to the above mentioned microgalvanic nature of the processes taking place, the influence of the corrosive media on the FCG curves is extremely required.…”
Section: Introductionmentioning
confidence: 99%
“…The AA2524-T3 (Solution Heat Treated and Cold Worked) alloy produced by ALCOA may be used as fuselage skin material and represents a potential replacement for the AA2024 alloy, widely used by the aircraft industry [11][12][13][14][15] . Recent studies 11,14,10 have shown that the fatigue behaviour of the AA2524-T3 alloy depends on experimental conditions (eg, applied stress, loading rate, environment as well as the crystalline orientation of the sample).…”
Section: Introductionmentioning
confidence: 99%
“…The AA2524-T3 (Solution Heat Treated and Cold Worked) alloy produced by ALCOA may be used as fuselage skin material and represents a potential replacement for the AA2024 alloy, widely used by the aircraft industry [11][12][13][14][15] . Recent studies 11,14,10 have shown that the fatigue behaviour of the AA2524-T3 alloy depends on experimental conditions (eg, applied stress, loading rate, environment as well as the crystalline orientation of the sample). With regarding to the electrochemical tests, it was possible to verify that the corrosion potential (E corr ) and the pit nucleation potential (E pit ) values are quite similar and the variation in the ratio of passive/active areas and/or cathode/anode, which may be related to the presence of different types of IMs 12,15 .…”
Section: Introductionmentioning
confidence: 99%